1996
DOI: 10.1111/j.1476-5381.1996.tb16716.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic actions of renal dopamine and 5‐ hydroxytryptamine: increase in Na+, K+‐ATPase activity in renal proximal tubules via activation of 5‐HT1A receptors

Abstract: 1 5-Hydroxytryptamine (5-HT) is antinatriuretic. Since this effect-of 5-HT is not accomplished by changes in glomerular haemodynamics, we have examined in this study whether 5-HT may influence sodium excretion by affecting the Na+, K+-ATPase activity in renal cortical tubules. 2 Na+, K+-ATPase activity was determined as the rate of [32P]-ATP hydrolysis in renal cortical tubules in suspension. Basal Na+,K+-ATPase activity in renal tubules was 4.8+0.4 imol Pi mg-' protein h-' (n = 8). The 5-HTA receptor agonist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Hence, for the purpose of this investigation, it seems most important to obtain a satisfactory MAO-A inhibition. It has been reported that 5-hydroxytryptamine (5-HT) is formed endogenously in proximal tubular cells [16] and exerts antinatriuretic effects via 5-HT 1A receptors by increasing the activity of Na + ,K + -ATPase [28]. In contrast to COMT, MAO also metabolizes 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, for the purpose of this investigation, it seems most important to obtain a satisfactory MAO-A inhibition. It has been reported that 5-hydroxytryptamine (5-HT) is formed endogenously in proximal tubular cells [16] and exerts antinatriuretic effects via 5-HT 1A receptors by increasing the activity of Na + ,K + -ATPase [28]. In contrast to COMT, MAO also metabolizes 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…Since the energy for tubular sodium reabsorption is supplied by the Na + ,K + ‐ATPase, it might then be suggested that stimulation of tubular sodium absorption by serotonin would involve activation of the Na + ,K + ‐ATPase. Indeed, Soares da Silva et al . (1996b) demonstrated that stimulation of serotonin receptors with the specific agonist 8‐hydroxy‐2‐(di‐n‐propylamino) tetraline (8‐OH‐DPAT) induced an augmentation of Na + ,K + ‐ATPase activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the interplay between the antagonistic actions of the natriuretic dopamine and the anti‐natriuretic serotonin plays a major role in renal sodium and water excretion (Soares da Silva et al ., 1996b; Vieira‐Coelho et al ., 1997). Both amines modulate urinary sodium excretion without affecting renal haemodynamics (Itskowitz et al ., 1988; Li Kam Wa et al ., 1996; Siragy et al ., 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue DreDaration PCT fragments were prepared as described before (13). Tissue DreDaration PCT fragments were prepared as described before (13).…”
Section: Introductionmentioning
confidence: 99%